THE EFFECT OF PRODUCTION COSTS, OPERATIONAL COSTS, MARKETING COSTS AND PROMOTIONAL COSTS ON NET PROFIT WITH SALES VOLUME AS INTERVENING VARIABLES IN PT GUDANG GARAM TBK 2015-2019 - Dedi Suselo; Miftahur Rohmah (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2021)
Net income is a component for measuring the success of a company. Several factors that affect net income are the amount of production costs, operational costs, marketing costs and promotional costs incurred by the company. The purpose of this study is to discuss the effect of independent variables on production costs, operational costs, marketing costs and promotional costs on net income through sales volume as an intervening variable with the research object at PT Gudang Garam Tbk for the period 2015 to 2019. Analysis of the data used in This study uses the classical assumption test, multiple linear regression, path analysis test and for the hypothesis the t test and F test are used. The results show that partially production costs, operational costs, marketing costs and promotional costs have a significant effect on net income. Simultaneously production costs, operational costs, marketing costs, promotion costs and sales volume have a significant effect on net income. Sales volume is able to mediate between production costs, operational costs, marketing costs and promotion costs on net income. Suggestions for further researchers are to add variables related to the level of net income such as long-term debt or can use intervening variables other than sales volume in increasing net income such as selling prices